Menelaah Pandangan Jamaluddin Al-Afghani Tentang Teologi Rasional - Rido Putra; Arrasyid Arrasyid; Rosi Islamiyati; Rido Putra (Program studi Keagamaan Islam, 2022)
Jamaluddin al-Afghani (1838-1897) is one of the Islamic modernists who is famous for his slogan of Pan-Islamism. Apart from his discourse on Islam and politics, al-Afghani also developed a system of rational theology. This article will explore al-Afghani's rational theology, especially about reason and revelation and human actions. This article employs a qualitative, explorative-analytical method. This article concludes that in al-Afghani’s theology, reason and revelation are two sources of knowledge that do not contradict each other, which both lead to the truth. Regarding human action, al-Afghani maintains that human being has the power to determine what they want to achieve.